Food and Agriculture in PNG - Michael Bourke, R. (ANU Press, 2009)
Agriculture dominates the rural economy of Papua New Guinea (PNG). More than five million rural dwellers (80% of the population) earn a living from subsistence agriculture and selling crops in domestic and international markets. Many aspects of agriculture in PNG are described in this data-rich book. Topics include agricultural environments in which crops are grown; production of food crops, cash crops and animals; land use; soils; demography; migration; the macro-economic environment; gender issues; governance of agricultural institutions; and transport. The history of agriculture over the 50 000 years that PNG has been occupied by humans is summarised. Much of the information presented is not readily available within PNG. The book contains results of many new analyses, including a food budget for the entire nation. The text is supported by 165 tables and 215 maps and figures.